Ser-homem no mundo: uma vista d’olhos da fenomenologia existencial para masculinidades - Magalhães, Rodrigo Piva Coelho de (2021)
How does the constitution of masculinity come about? What is the moment when a person recognizes himself as a man, and what leads to this recognition? Is it possible that this recognition happens with a person alone, or is it inevitably a group process? And this group, how can it tell what it means to be a man? How does the recognition and reception of one man by others happen? Is it truly a welcoming process? The image that a certain group has of what it means to be a man is unchanging? Is it the same image the world round? Is it today the same image it was decades ago? How can a man recognize today his role in the dynamics of gender structure? This research aims to clarify such questions, starting from the analysis of the available literature around the topic of masculinity, with a focus on south american authors. Through these studies, we hope to construct a comprehension on how masculinity is built, and to explore how this phenomenon is stained by time, culture and language. In order to think about these elements, existential phenomenology is called to the center stage, especially the work of Martin Heidegger and Maurice Merleau-Ponty. These authors and others help us in reflecting on the method of a research work, as they accompany us on the questions about the access we can get to any phenomenon. Since this is a work on gender, it was necessary to search for the history of masculinity studies in Brazil, which leads us to the feminist struggle, analyzed here in the context of women’s fight to have their existence respected, studied and validated, as well as in the context of this fight’s consequences. These researchers lay the groundwork for the comprehension that the present dissertation offers on the constitution of masculinity. This comprehension is drawn over two interviews with two men living in the North region of São Paulo. In reflexive interviews, both reflect on what makes them men, and the analysis of these reflexions, based on existential phenomenology, is what the present dissertation offers